2022
DOI: 10.1186/s12886-022-02253-w
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopic characteristics of acute angle-closure crisis

Abstract: Background To investigate characteristics of the acute angle-closure crisis (AACC) and fellow eyes using confocal microscopy. Methods Unilateral AACC patients hospitalized at the Xi’an People’s Hospital from October 2017 to October 2020 were recruited in this cross-sectional study. Age-matched participants scheduled for cataract surgery were enrolled as a healthy control group. Corneal epithelial cells, subepithelial nerve fiber plexus, stromal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Corneal endothelium is a monolayer of hexagonal cells with no proliferative capacity, executing the function of a barrier and pump, so that cornea transparency can be preserved [ 5 ]. Previous research had observed significant corneal dysfunction after APAC and reported the percentage of cell density decrease between 9.7 and 35.1% [ 6 12 ]. However, in light of the published studies, a minimal endothelial cell density (ECD) is required to perform this duty [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Corneal endothelium is a monolayer of hexagonal cells with no proliferative capacity, executing the function of a barrier and pump, so that cornea transparency can be preserved [ 5 ]. Previous research had observed significant corneal dysfunction after APAC and reported the percentage of cell density decrease between 9.7 and 35.1% [ 6 12 ]. However, in light of the published studies, a minimal endothelial cell density (ECD) is required to perform this duty [ 13 ].…”
Section: Introductionmentioning
confidence: 99%